Review of the role of robotic surgery in male infertility - Mohamed Etafy (Taylor & Francis Group, 2018)
Objectives: To present the current state of the art in various robot-assisted microsurgical procedures in male infertility and review the latest literature, as the technology in infertility procedures has substantially developed since the incorporation of the Vinci® robotic platform (Intuitive Surgical, Inc., Sunnyvale, CA, USA). Materials and methods: The search strategy in this review was conducted in accordance with Cochrane guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A search strategy was conducted in MEDLINE, PubMed and the Cochrane electronic databases (from 2000 to present) to identify studies that included both robotic and male infertility. Results: In all, 23 studies were found, 12 of which met our inclusion criteria. Articles were excluded if the study did not include both male infertility and robotics. Conclusions: Robotic assistance for microsurgical procedures in male infertility appears to be safe and feasible. It has several advantages including elimination of tremor, multi-view magnification, additional instrument arms, and enhanced dexterity with articulating instrument arms. It also has a short learning curve with a small skin incision. However, larger, prospective studies are needed to establish the clinical benefits over standard microsurgery. Keywords: Robotic testicular sperm extraction, Robotic varicocelectomy, Robotic vasectomy reversal, Robotic vasoepididymostomy (RAVE), Robotic vasovasostomy